Modern Forms of Bank Service in Albania - Gjermizi, Jehona; Dr. Blerim Kola (European Journal of Multidisciplinary Studies, 2016)
Albanian banks are currently implementing e-banking. Banks that offer service via this channel claim that it reduces costs and makes them more competitive. However, many corporate consumers are not highly enthusiastic about Internet banking. An understanding of why corporate customers do not accept Internet banking can assist banks to implement this self-service technology more efficiently. In-depth qualitative interviews with Albanian firms suggest that security of the internet is a major factor inhibiting wider adoption. Those already using Internet banking seem to have more confidence that the system is reliable,whereas non-users are much more service conscious,and do not trust financial transactions made via Internet channels. Non-internet banking users tend to have more negative management attitudes toward adoption and are more likely to claim lack of resources. Legal support is also a major barrier to Internet banking adoption for corporate customers.